Report on MNT campaign: July 15-September 14, 2001 - BRAC (© BRAC, 2016)
1. Introduction & background 2. Organizational background 3. BRAC in partnership with SNL initiatives 4. BRAC MNT facilitator 5. Accomplishment of campaign action plan 6. MNT orientation & social mobilization 7. Management support 8. Achievement status